Azithromycin in the treatment of the early syphilis during pregnancy - Passos, Mauro R.L.; Bravo, Renato S.; Barreto, Nero A.; Varella, Renata Q.; Santos, Cláudio C.C.; Nascimento, Auri V.S.; Morelli, Maurício H. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
The authors present some cases in which pregnant patients with early syphilis (papular syphilides) presented impediments to the use of penicillin G benzathine e and were treated with azithromicin 1g/week for 3 weeks. Two patients showed the prozone phenomenon at V.D.R.L serology. All envolved to clinical and serological cure. No showed clinical or serological signs of syphilitic infection or other abnormalities after birth. No important secondary effects were noted.